2016
DOI: 10.1007/s11064-016-1989-7
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin Activates Apoptosis via Inhibition of PI3K/Akt/mTOR Pathway and Suppresses Invasion and Migration by Restriction of p38-MMP-2/9 Pathway in Human Glioblastoma Cells

Abstract: Fucoxanthin is rich in seaweed and considered as effective anti-cancer drug because of powerful antioxidant properties. The objective of this study was to investigate the role of fucoxanthin on apoptosis, invasion and migration of glioma cells. Firstly, fucoxanthin showed obvious cytotoxicity against human glioma cancer cell line U87 and U251, however, there was no inhibitory effect on normal neuron. And then, fucoxanthin induced apoptotic cell death showed by the condensation of chromatin material stained wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
62
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 50 publications
7
62
0
1
Order By: Relevance
“…In vitro studies indicate that fucoxanthin stimulates apoptosis and decreases proliferation and migration in glioma cancer cell lines U87 and U251 through Akt/mTOR and p38 pathway inhibition [82]. Fucoxanthin intake may have health benefits for the treatment of Alzheimer's disease by inhibiting acetylcholinesterase and enhancing brain-derived neurotrophic factor expression [83].…”
Section: Antioxidant Functions Of Carotenoids At Molecular Level For mentioning
confidence: 99%
“…In vitro studies indicate that fucoxanthin stimulates apoptosis and decreases proliferation and migration in glioma cancer cell lines U87 and U251 through Akt/mTOR and p38 pathway inhibition [82]. Fucoxanthin intake may have health benefits for the treatment of Alzheimer's disease by inhibiting acetylcholinesterase and enhancing brain-derived neurotrophic factor expression [83].…”
Section: Antioxidant Functions Of Carotenoids At Molecular Level For mentioning
confidence: 99%
“…Previous studies have focused on the role of fucoxanthin in cancer treatment and health protection. For example, fucoxanthin was shown to augment apoptosis, reduce cell proliferation, migration and invasion in human glioblastoma cell lines14. Furthermore, fucoxanthin in diet significantly reduced weight gain in animals through increasing fatty acid oxidation and heart production in white adipose tissue15.…”
mentioning
confidence: 99%
“…A recent review summarized that fucoxanthin and phloroglucinol in edible seaweed were found to be cytotoxic against glioblastoma in in vitro and in vivo . Liu et al showed that fucoxanthin decreased cell viability and caused up to 40% apoptosis when treated U251MG and U87MG cells with 50 μM for 24 hours . Cho et al reported their cell cycle analysis after a 16 hour treatment with 50 μg/mL of Pa, recording the population in G0/G1 phase increased (12.5%), sub‐G1 fraction cells increased (19.2%) and in G2/M phase decreased (10%) only .…”
Section: Discussionmentioning
confidence: 99%
“…11 Liu et al showed that fucoxanthin decreased cell viability and caused up to 40% apoptosis when treated U251MG and U87MG cells with 50 μM for 24 hours. 12 Cho et al reported their cell cycle analysis after a 16 hour treatment with 50 μg/mL of Pa, recording the population in G0/G1 phase increased (12.5%), sub-G1 fraction cells increased (19.2%) and in G2/M phase decreased (10%) only. 13 15 Our study consistently showed that EOla in low concentrations (<1:100 dilution) had very low cytotoxicity on glioblastoma cells.…”
Section: Discussionmentioning
confidence: 99%